Cata-annulated azaacene bisimides - Elter, Maximilian; Ahrens, Lukas; Luo, Stella M.; Rominger, Frank; Freudenberg, Jan; Cao, Dennis D.; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
Ultra-electron-deficient azaacenes were synthesized via Buchwald-Hartwig coupling of ortho-diaminoarenes with chlorinated mellophanic diimide followed by oxidation of the intermediate N,N’-dihydro compounds with MnO2 or PbO2. The resulting cata-annulated bisimide azaacenes have ultrahigh electron affinities with first reduction potentials as low as −0.35 V recorded for a tetraazapentacene. Attempts to prepare a tetrakis(dicarboximide)tetraazaheptacene resulted in the formation of a symmetric butterfly dimer.
Gesehen am 03.04.2023